Sensorless Control System Design of a Small Size Vertical Axis Wind Turbine - Mayouf., Messaoud (Université de M'sila, 2018)
This paper describes control system design of a small size vertical axis wind turbine for battery charging, using permanent magnet synchronous generator (PMSG). The direct drive PMSG is connected to the battery through a switch mode rectifier where a DC-DC buck converter is used to optimize the wind power. The use of speed sensor to the control system design complicates and adds more costs to the system. To resolve this problem, a sensorless maximum power-tracking algorithm is proposed to calculate the current command that corresponds to maximum power output of the turbine. The DC-DC converter uses this current command to calculate the duty cycle which is necessary to control the pulse width modulated (PWM) active switching device. The system overview and modeling is presented, including characteristics of wind turbine, generator, batteries, power converter, control system, and supervisory system. A simulation of the system is performed using MATLAB/SIMULINK
Keywords: Battery charging, Permanent magnet synchronous generator (PMSG), vertical axis wind turbine, maximum power point tracking (MPPT),PWM DC-DC buck converter.